Contribution to the Sensorless Mechanical Control of a Variable Reluctance Synchronous Machine - Gati Miloud (University Eloued جامعة الوادي, 2025)
This thesis focuses on variable speed synchronous machine drives, highlighting their advantages such as robustness and high reliability. Previous research has explored variable speed control of these drives, particularly for applications such as rail traction and marine propulsion. Many problems require the estimation of the state of a system using an observer. However, modelling and synthesising the observer becomes a difficult task for non-linear systems. Synchronous Variable Reluctance Machines (SynRMs) have advantages, but their control can be complex due to model non-linearity and parameter fluctuations. The research presented in this thesis focuses on the state estimation of non-linear systems represented by an Mras-Mpc controller which is proposed as the newest strategy, it combines all cascade structures into one control law to obtain the switching vector by minimising the predefined cost function. After an introduction to predictive control (MPC) and the optimisation criterion, the Mras is presented in detail while developing its stability in order to propose two approaches with two different cost functions combining the two observers into a single one to consolidate the quantities to be estimated. The first approach consists of feeding the input quantities of the predictive control model with the output quantities of the model's reference adaptive system, in order to achieve the optimum speed. In the second approach, we propose a controller that estimates the speed by replacing traditional PI controllers with a predictive control model that calculates a new speed estimate based on the MRAS scheme using only stator current and voltage measurements and then optimises the vector voltage that minimises the current error. الملخص: تركز هذه الأطروحة على محركات الماكينات المتغيرة السرعة المتزامنة مع تسليط الضوء على مزاياها مثل المتانة والموثوقية العالية. وقد تناولت الأبحاث السابقة التحكم في السر عة المتغيرة لهذه المحركات خاصةً في تطبيقات مثل الجر بالسكك الحديدية وعملية الدفع البحري . تتطلب العديد من المسائل تقدير حالة النظام باستخدام مراقب. ومع ذلك تصبح نمذجة المراقب وتوليفه مهمة صعبة بالنسبة للأنظمة غير الخطية. تتمتع آلات الممانعة المتغيرة المتزامنة (SynRMs) بمزايا ولكن يمكن أن يكون التحكم فيها معقدًا بسبب عدم خطية النموذج وتذبذب المتغيرات. يركز البحث المقدم في هذه الأطروحة على تقدير حالة الأنظمة غير الخطية المتمثلة في وحدة تحكم Mras - Mpc المقترحة كأحدث استراتيجية فهي تجمع بين هاتين البنيتين المتتاليتين في قانون تحكم واحد للحصول على شعاع التبديل عن طريق تقليل دالة التكلفة المحددة مسبقًا.. بعد مقدمة عن التحكم التنبؤي MPC و معيار التحسين يتم عرض نظام Mras بالتفصيل مع تطوير استقراره من أجل اقتراح طريقتين بدالتين مختلفتين للتكلفة تجمعان بين المراقبين في مراقب واحد لتوحيد المقادير المراد قياسها وذلك من أجل تحقيق السرعة المثلى.. يتكون النهج الأول من تغذية كميات مدخلات نموذج التحكم التنبؤي بكميات مخرجات النظام التكيفي المرجعي للنموذج من أجل تحقيق السرعة النموذجية. في النهج الثاني نقترح وحدة تحكم تقوم بتقدير السرعة عن طريق استبدال وحدات التحكم PIالتقليدية بنموذج تحكم تنبؤي يقوم بحساب تقدير جديد للسرعة بناءً على مخطط MRAS باستخدام قياسات تيار الجزء الثابت والتوتر الكهربائي فقط ثم تحسين شعاع التوتر الذي يقلل من خطأ التيار Résumé :فرنسية أو انجلزية This thesis focuses on variable speed synchronous machine drives, highlighting their advantages such as robustness and high reliability. Previous research has explored variable speed control of these drives, particularly for applications such as rail traction and marine propulsion. Many problems require the estimation of the state of a system using an observer. However, modelling and synthesising the observer becomes a difficult task for non-linear systems. Synchronous Variable Reluctance Machines (SynRMs) have advantages, but their control can be complex due to model non-linearity and parameter fluctuations. The research presented in this thesis focuses on the state estimation of non-linear systems represented by an Mras-Mpc controller which is proposed as the newest strategy, it combines all cascade structures into one control law to obtain the switching vector by minimising the predefined cost function. After an introduction to predictive control (MPC) and the optimisation criterion, the Mras is presented in detail while developing its stability in order to propose two approaches with two different cost functions combining the two observers into a single one to consolidate the quantities to be estimated. The first approach consists of feeding the input quantities of the predictive control model with the output quantities of the model's reference adaptive system, in order to achieve the optimum speed. In the second approach, we propose a controller that estimates the speed by replacing traditional PI controllers with a predictive control model that calculates a new speed estimate based on the MRAS scheme using only stator current and voltage measurements and then optimises the vector voltage that minimises the current error.
Contribution à la commande sans capteur mécanique de la machine synchrone à réluctance variable
Thèse de Doctorat
Keywords: Sensorless Control; Synchronous reluctance machine; Model Reference Adaptive System; model predictive control; Direct Vector Control; Pulse Width Modulation; predictive; Lyapunov stability; التحكم بدون مستشعر; الماكنات الكهربائية ذات المغناطسية المتغيرة; النظام التكيف المرجعي النمطي; التحكم بالشعاع المباشر; التحكم التنبئي; استقرار ليابونوف